Bilateral Breast Metastases from Rectal Carcinoma: A Rare Case of Rapid Dissemination in a Young Female Detected by FDG PET-CT (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Breast metastases from rectal carcinoma are incredibly uncommon. Here we describe a patient with metastatic deposits in the breast from rectal carcinoma and the pattern of disseminated metastases within one year after the initial diagnosis. Case Summary: A 28-year-old female patient was diagnosed with rectal carcinoma in February 2023 and underwent surgery in the following March followed by radiotherapy in June and completed chemotherapy in November 2023. Her first PET-CT scan was done in November 2023, due to the rising tumor marker (CEA), which showed two suspicious, ill-defined, soft tissue density hypermetabolic areas in the left breast along with a hypermetabolic right lower cervical lymph node. A focal hypermetabolic intercostal muscle nodule was noted in the right tenth intercostal region. Histopathology and immunohistochemistry from the left breast mass showed metastatic, poorly differentiated carcinoma. Two weeks after the PET-CT scan, the patient suddenly developed chest pain, breathing difficulty, and a hard lump in both breasts. To assess the disease progression, another PET-CT scan was done in January 2024. The second PET-CT scan showed morpho-metabolic progression of prior left breast mass lesions along with newly developed hypermetabolic mass lesions in the right breast & right chest wall. Metastatic right lower cervical, left axillary, and abdominal lymph nodes with metabolic progression were also noted. Metabolic progression of the prior intercostal muscle nodule in the right tenth intercostal region with a newly developed hypermetabolic subcutaneous nodule was seen in the right posterior chest wall. Newly developed metastatic hypermetabolic peritoneal deposits and hepatic metastases were also evident along with bilateral moderate pleural effusions and mild ascites. The patient succumbed to the disease a few months after receiving palliative chemotherapy along with conservative and symptomatic management. Conclusion: Metastatic rectal carcinoma to the breast indicates a highly aggressive tumor. In this case report, the FDG PET-CT scan showed an unusual metastatic pattern and rapid aggressive dissemination within a short period.Bangladesh J. Nuclear Med. 27(2): 284-289, 2024